The visual as an event: spect-acting gender in Out of a Doll's House. Issue 3 (2nd October 2021) - Yerushalmi, Dorit
Abstract: Theatre is an image producer that is embedded with cultural practices of looking and critically involved in modes of looking. This case study offers an analysis of Out of a Doll's House, a post-dramatic feminist performance. It demonstrates the manner in which visual dramaturgy exposes spectators to the process of performing an image as an action, and to the mechanism of constructing a theatrical image as a reflexive event. The analysis explores how visual post-dramatic dramaturgy allows participants to observe and experiment with gender as performance and with the visual as an event.